ABOUTHE THE MODERNISATION OF HISTORY (THE LESSONS OF DISCUSSION IN 60-70 YEARS IN WESTERN PHILOSOPHY AND THE MENODOLOGY OF HISTORY) - Синяков, С. В.; Сластенко, Е. Ф. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to the analysis of value-normative aspects of historical cognition: the problems of historical interpretations, political and ideological substantiation and truthfulness of historical knowledge, coincidence of history and present time.